Fatty Amidine as Copper Corrosion Inhibitor - Zainal Alim Mas’ud; Noviyan Darmawan; Januari Dawolo; Yusuf Bramastya Apriliyanto (Journal of Chemistry)
The development of green and sustainable corrosion inhibitors for copper in a corrosive marine environment is highly desired. Herein, we studied the fatty acid-based amidine as the new type of renewable corrosion inhibitor. Stearamidine salt was used as a model inhibitor, and it was synthesized through stearonitrile intermediate with an excellent isolated yield of 88%. We used electrochemical (potentiodynamic polarization) and morphological (scanning electron microscopy) measurements to assess the corrosion inhibition efficiency of stearamidine in 3.0 wt.% NaCl at 300 K. We show that, in such a condition, the optimum inhibition efficiency of 96% was achieved using only 0.2 mM stearamidine. The results suggested the fatty amidine is a promising corrosion inhibitor for copper that is suitable in the saltwater ecosystem. The thermodynamic parameters of the interaction between the stearamidine and the copper surface were determined, and the result suggests that the adsorption process occurred accordingly with the Langmuir adsorption isotherm and involved both physisorption and chemisorption.